Educational game model in Mathematics learning for private classes - Astuti, Prilia Linda; Ferawati, Denny Indria; Mentari, Ika (DRPM UNY, 2025)
In the context of private tutoring, innovative learning approaches are crucial for enhancing students' engagement and academic success. This study explores the application of educational games in mathematics learning within private tutoring sessions. Educational games, which combine elements of play with educational content, offer a more engaging and personalized method of instruction. The study focuses on the implementation of various game models, such as Snakes and Ladders, Ludo, Math Cards, and Trimino, to improve students' understanding of mathematical concepts in private settings. The findings demonstrate that these games can create a relaxed, enjoyable learning atmosphere, which increases student motivation, enhances their understanding, and boosts their interest in learning mathematics. By incorporating interactive elements, educational games support the development of critical mathematical skills, including numeracy, logical thinking, and problem-solving. Furthermore, these games foster active participation, which is essential for sustaining student engagement, particularly in one-on-one tutoring environments. Through the use of games, private tutors can tailor learning experiences to meet the individual needs of students, providing a more adaptive and effective educational experience.